Emerging Private Education in Turkey : Determinants of Social Choice Via Houshold's Characteristics - Yanık İlhan, Bengi; GÜMÜŞOĞLU, NEBİLE KORUCU (My University, 2019)
Human capital is one of the crucial factors for growth and development. From this point of view, having equal educational opportunities should be ensured by governments. However, in most of the developing countries like Turkey, having equal educational opportunities seems as a phantasy. In this manner, the main aim of this study is to try to find out the determinants of school choices in Turkey and secondly to analyze if there are any gender differences or not. This choice is probably related to household’s choice, it is not a child’s choice. We use the youth survey conducted in Turkey in 2011 for 2366 youth in 35 selected provinces. The descriptive statistics of the sample is also presented to see the main picture of Turkey. Controlling the household characteristics such as father’s labor market situation, education, household’s income, household’s religious values, living areas and region, our first findings shows that for the case of males household income does not have an impact on being in a private education. However, it does have a significant effect for females. Interestingly, most of the regions do not have an impact on being in a private school. However, being in Aegean region does have a negative effect on being in a private school for males. Generally, for boys, it can be said that private school choice does not depend controlled variables. It means that households prefer sending their boys to private schools whatever their situation and whatever their characteristics. On the other hand, for girls there are many factors that can affect on choosing private schools.
Keywords: Private Schools; Turkey; School Choice; Gender; Özel Okullar; Türkiye; Okul Seçimi; Cinsiyet